2022
DOI: 10.3390/ijms23137375
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Phenylpropanoid Biosynthesis Lead to the Natural Formation of Pinkish-Skinned and White-Fleshed Strawberry (Fragaria × ananassa)

Abstract: Anthocyanin content is important for both the external and internal fruit quality of cultivated strawberries, but the mechanism of its accumulation in pinkish-skinned and white-fleshed strawberries is puzzling. Here, we found that the factor determining variation in the flesh color was not the FaMYB10 but the FaC4H in the cultivated strawberry Benihoppe and its white-fleshed mutant Xiaobai. Compared with Benihoppe, there was no significant difference in the coding sequence and expression level of FaMYB10 in Xi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Jiang et al. also performed comparative transcriptomic analysis of HJ and XB ripe fleshed, and suggested that the repression of FaC4H was responsible for lack of anthocyanin in XB ripe flesh ( Jiang et al., 2022 ). FaC4H is a key gene in the phenylpropanoid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al. also performed comparative transcriptomic analysis of HJ and XB ripe fleshed, and suggested that the repression of FaC4H was responsible for lack of anthocyanin in XB ripe flesh ( Jiang et al., 2022 ). FaC4H is a key gene in the phenylpropanoid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, FaUFGT was clearly differentially expressed (upregulated more than twenty-fold), suggesting that it contributed to the different flesh colors between HJ and XB. Jiang et al also performed comparative transcriptomic analysis of HJ and XB ripe fleshed, and suggested that the repression of FaC4H was responsible for lack of anthocyanin in XB ripe flesh (Jiang et al, 2022). FaC4H is a key gene in the phenylpropanoid metabolic pathway.…”
Section: Essential Role Played By Faufgt In the Biosynthesis Of Antho...mentioning
confidence: 99%
“…The relative expression of FaU-box genes was calculated using the 2 -ΔΔCt method ( Livak and Schmittgen, 2001 ). FaActin (accession: LC017712) and 26-18S interspacer RNA ( Jiang et al., 2022 ) were used as the reference genes to normalize the raw expression data. All data were represented by the mean ± standard deviation (SD) of three independent biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…At least two well replicates were performed for each sample, and threeindependent cDNA samples were used as three biological replicates. The primers of flavonoid-related and housekeeping genes were the same as used in a previous study [ 64 ]; other primers were designed using NCBI online tool; all primers are listed in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%